A method for preparing positive electrode material based on supercritical carbon dioxide solution, positive electrode material and secondary battery
Preparing the cathode material through supercritical carbon dioxide solution solves the problems of high cost and heavy pollution in traditional methods, and realizes efficient and low-cost cathode material preparation, improving the electrochemical performance and life of the secondary battery.
Patent Information
- Application Number
- CN202310056830.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-17
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-01-17
AI Technical Summary
The commercial preparation method of traditional cathode materials is high cost, heavy pollution and complex process flow, resulting in poor functionality of cathode materials and unable to meet the energy density requirements of secondary batteries.
The supercritical carbon dioxide solution is used as the reaction medium to prepare the positive electrode material through hydrothermal reaction and high-temperature calcination. A coupled reaction system is formed using carbonate and alcohol solvents to regulate crystal growth and obtain a positive electrode material with uniform particle size distribution and complete structure.
The preparation process is simple, low cost and environmentally friendly. The obtained positive electrode material shows excellent electrochemical performance in secondary batteries, improves battery life and is suitable for large-scale applications.
Smart Images

Figure HDA0004060661450000011 
Figure HDA0004060661450000012 
Figure HDA0004060661450000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new energy materials and devices, and relates to a method for preparing a positive electrode material based on a supercritical carbon dioxide solution, a positive electrode material and a secondary battery. Background Art
[0002] In recent years, secondary battery technology has developed rapidly in the fields of electric vehicles and energy storage power stations due to its advantages such as high operating voltage, long cycle life and low environmental pollution. It is considered to be the energy storage technology with the most development potential in the future. However, the vigorous development of industries such as electric vehicles and energy storage power stations has put forward more stringent requirements for secondary battery technology, such as higher energy density, better safety performance, and lower production costs. A large number of studies have found that positive electrode materials, as an important component of secondary batteries, are the key to breaking through their performance bottlenecks. At present, the commercial preparation methods of traditional positive electrode materials have the disadvantages of high cost, heavy pollution, and complex process flow. The obtained positive electrode materials have poor functionality and low capacity, and cannot further meet the energy density requirements of secondary ion batteries. Therefore, it is necessary to develop new positive electrode material preparation process technologies. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a positive electrode material based on a supercritical carbon dioxide solution, a positive electrode material and a secondary battery. The method has the characteristics of high efficiency, simple operation, low cost and environmental friendliness. The final positive electrode material obtained shows excellent electrochemical performance when used in a secondary battery, greatly improves the life of the secondary battery, and is suitable for large-scale engineering applications.
[0004] The present invention is achieved through the following technical solutions:
[0005] A method for preparing a positive electrode material based on a supercritical carbon dioxide solution comprises the following steps:
[0006] S1, adding a carbon dioxide initiator, a transition metal salt, an alkali metal salt and an alcohol solvent into water, mixing to obtain a mixed solution;
[0007] S2, subjecting the mixed solution to a hydrothermal reaction, washing and drying the obtained product to obtain a hydrothermal product;
[0008] S3, calcining the hydrothermal product at high temperature to obtain a precursor;
[0009] S4, mixing the precursor with lithium salt, and calcining at high temperature to obtain the positive electrode material.
[0010] Preferably, in S1, the carbon dioxide initiator is one or more of urea, urotropine, Na2CO3, NaHCO3, dry ice, NH4HCO3 and oxalic acid; the transition metal salt is one or more of NiCl2, CoCl2, MnCl2, Ni(NO3)2, Co(NO3)2, Mn(NO3)2, Ni(CH3COO)2, Co(CH3COO)2 and Mn(CH3COO)2.
[0011] Preferably, in S1, the alkali metal salt is one or more of LiNO3, NaNO3, KNO3, LiOH, NaOH, KOH, Li2CO3, Na2CO3, K2CO3, CH3COOLi, CH3COONa, CH3COOK, LiCl, NaCl and KCl; and the alcohol solvent is an alcohol having a carbon number of less than ten.
[0012] Preferably, in S1, the molar ratio of the carbon dioxide initiator to the transition metal salt is (0.1-4):1; when an alkali metal salt is added, the molar ratio of the alkali metal salt to the transition metal salt is (0.01-1):1; when an alcohol solvent is added, the volume ratio of the alcohol solvent to water is 1:(0.1-10).
[0013] Preferably, in S2, the hydrothermal reaction temperature is 110-200° C., and the reaction time is 20 h to 28 h.
[0014] Preferably, in S3, high-temperature calcination is carried out in air or oxygen atmosphere, the calcination temperature is 300 to 1200° C., and the time is 5 to 48 hours.
[0015] Preferably, in S4, the lithium salt is one or more of LiNO3, NaNO3, KNO3, LiOH, NaOH, KOH, Li2CO3, Na2CO3, K2CO3, CH3COOLi, CH3COONa, CH3COOK, LiCl, NaCl and KCl.
[0016] Preferably, in S4, high-temperature calcination is carried out in air or oxygen atmosphere, the calcination temperature is 700-1200° C., and the time is 10-72 hours.
[0017] The positive electrode material is obtained by using the positive electrode material preparation method based on supercritical carbon dioxide solution.
[0018] A secondary battery comprises the positive electrode material.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention is based on the positive electrode material preparation method of supercritical carbon dioxide solution, carbon dioxide initiator, transition metal salt and alkali metal salt and alcohol solvent are added to water to prepare a uniform mixed solution, and a supercritical carbon dioxide solution is obtained by changing the concentration of carbon dioxide initiator, wherein the alkali metal salt has the regulation effect of crystal anisotropic growth, and forms a coupling reaction system with low-carbon chain alcohol solvent to reduce the heterogeneous nucleation reaction energy barrier; the mixed solution is reacted under high temperature and high pressure conditions to obtain a transition metal precursor with uniform particle size distribution; the precursor is subjected to lithium and high temperature heat treatment, and finally obtains a positive electrode material with uniform particle size distribution, complete particle structure, large tap density and good structural stability, which can be used to prepare secondary batteries with excellent cycle performance and rate performance; compared with the current traditional commercial preparation method, the preparation method of the present invention has the outstanding advantages of simple preparation process, low cost, easy large-scale amplification, and the precursor product with complete crystal form, uniform particle size distribution and diversified functions can be obtained without the need for long-term high temperature treatment. More importantly, there is no need to add a large amount of acid and alkali reagents during the synthesis process, which is pollution-free to the environment and further reduces the production cost.
[0021] The positive electrode material obtained by the method of the present invention has the advantages of uniform particle size distribution, complete particle structure, large tap density, good structural stability, high purity, high yield, and adjustable morphology and size.
[0022] The positive electrode material obtained by the present invention exhibits excellent electrochemical performance when used in secondary batteries, greatly improves the life of the secondary batteries, and is suitable for large-scale engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the SEM image and element mapping image of the cathode material precursor obtained in Example 1 of the present invention;
[0024] Figure 2 is a SEM image of the positive electrode material obtained in Example 1 of the present invention;
[0025] Figure 3 is a SEM image of the precursor material prepared in Example 6 of the present invention;
[0026] Figure 4 is a SEM image of the positive electrode material prepared in Example 10 of the present invention;
[0027] Figure 5 is a SEM image of the positive electrode material prepared in Example 11 of the present invention;
[0028] Figure 6 This is a SEM image of a precursor material prepared in a comparative example of the present invention;
[0029] Figure 7This is an electrochemical performance diagram of the positive electrode material prepared in Example 1 of the present invention applied to a button battery;
[0030] Figure 8 It is an electrochemical performance diagram of the positive electrode materials prepared in the comparative example and Example 6 of the present invention when applied to button batteries. DETAILED DESCRIPTION
[0031] In order to further understand the present invention, the present invention is described below in conjunction with embodiments. These descriptions are only to further explain the features and advantages of the present invention and are not intended to limit the claims of the present invention.
[0032] The present invention provides a method for preparing a cathode material based on a supercritical carbon dioxide solution, comprising the following steps:
[0033] Step 1, dissolving a carbon dioxide initiator and a transition metal salt in deionized water, and mixing at room temperature to obtain a uniform solution 1;
[0034] Step 2, adding an alkali metal salt and an alcohol solvent to the uniform solution 1 obtained in step 1, and mixing at room temperature to obtain a uniform solution 2;
[0035] Step 3, transferring the uniform solution 2 obtained in step 2 to a high pressure reactor for reaction;
[0036] Step 4, washing, filtering and then drying the product obtained in step 3;
[0037] Step 5, calcining the product after drying in step 4 at high temperature to obtain a precursor;
[0038] Step 6, uniformly mixing the precursor obtained in step 5 with an alkali metal lithium salt, calcining at high temperature, and naturally cooling to obtain a positive electrode material.
[0039] In step 1, the carbon dioxide initiator is urea (CH4N2O), urotropine (C6H 12 N4), Na2CO3, NaHCO3, dry ice, NH4HCO3 and oxalic acid (C2H2O4), the transition metal salt is one or more of NiCl2, CoCl2, MnCl2, Ni(NO3)2, Co(NO3)2, Mn(NO3)2, Ni(CH3COO)2, Co(CH3COO)2 and Mn(CH3COO)2, the concentration of the transition metal salt solution is 0.001-2 mol / L, the molar ratio of the carbon dioxide initiator to the transition metal salt is (0.1-4):1, the mixing method is one or more of mechanical stirring, magnetic stirring and ultrasound, and the mixing time is 0.1-12h.
[0040] In step 2, the alkali metal salt is one or more of LiNO3, NaNO3, KNO3, LiOH, NaOH, KOH, Li2CO3, Na2CO3, K2CO3, LiCH3COOH, NaCH3COOH, KCH3COOH, LiCl, NaCl, and KCl, the molar ratio of the alkali metal salt to the transition metal salt in step 1 is (0.01-1):1, the alcohol solvent is one of the alcohols having a carbon number of ten or less, the volume ratio of the alcohol solvent to the deionized water in step 1 is 1:(0.1-10), the solution mixing method is one or more of mechanical stirring, magnetic stirring, and ultrasound, and the mixing time is 0.1-12h.
[0041] In step 3, the high-pressure hydrothermal reaction temperature is 110-200° C., the reaction time is 20-28 hours, the high-pressure reaction container is made of stainless steel or polytetrafluoroethylene, the volume is 0.1-50 L, and the reaction pressure is 1-100 MPa.
[0042] In step 4, the product is washed with ethanol for 3 to 5 times and dried in a forced air oven at 40 to 120° C. for 2 to 12 hours.
[0043] In step 5, the high-temperature calcination process is carried out in a muffle furnace / box furnace with an air / oxygen atmosphere, the heat treatment temperature is 300 to 1200° C., and the insulation time is 5 to 48 hours.
[0044] In step 6, the alkali metal lithium salt used is one or more of LiNO3, NaNO3, KNO3, LiOH, NaOH, KOH, Li2CO3, Na2CO3, K2CO3, CH3COOLi, CH3COONa, CH3COOK, LiCl, NaCl, and KCl. The planetary ball milling method is adopted, the mixing time is 1 to 24 hours, the ball-to-material mass ratio is (1 to 200): 1, and the high-temperature calcination process is carried out in a muffle furnace / box furnace with an air / oxygen atmosphere. The heat treatment temperature is 700 to 1200°C and the insulation time is 10 to 72 hours.
[0045] The cathode material precursor prepared by the present invention based on supercritical carbon dioxide solution has a variety of morphological structures. By changing the type and amount of alcohol solvent, microsphere-shaped, petal-shaped, and cauliflower-shaped precursors with a diameter of 1 to 15 μm can be obtained. After high-temperature heat treatment, the original morphological structure can still be maintained and the cathode material has good stability. The application fields of the obtained cathode material include energy conversion and energy storage, photocatalysis, electrocatalysis, photoelectrocatalysis, adsorption, gas sensing, photoluminescence, etc. For example, it can be used as a cathode material for secondary batteries.
[0046] Embodiment 1:
[0047] Step 1: 0.02 mol C6H12 N4, 0.002 mol Ni(CH3COO)2, and 0.006 mol Mn(CH3COO)2 were dissolved in 30 mL of deionized water and stirred at room temperature for 10 min to obtain a homogeneous solution;
[0048] Step 2, adding 0.001 mol CH3COOLi and 40 mL ethanol to the solution obtained in step 1, and stirring to obtain a uniform solution;
[0049] Step 3, transferring the uniform solution obtained in step 2 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 160° C. for 24 h, and then cooling naturally to room temperature;
[0050] Step 4, washing the product obtained in step 3 with ethanol three times and filtering it, placing it in a forced air oven, and drying it at 80° C. for 2 h to obtain a solid powder;
[0051] Step 5, placing the solid powder obtained in step 4 into a muffle furnace and keeping the temperature at 480° C. for 5 h to obtain a precursor;
[0052] Step 6: Grind and mix 0.2 g of the precursor obtained in step 5 with 0.152 g of LiOH·H2O, put it into a muffle furnace, keep it at 780°C for 12 h, and cool it naturally to room temperature to obtain a petal-shaped Li 1.2 Ni 0.2 Mn 0.6 O2 positive electrode material.
[0053] The positive electrode material prepared by the above embodiment has a conductivity of 2.1 g / cm 3 The high tap density and the element content analysis (ICP) results show that the ratio of Ni to Mn is 1:2.98, which is close to the theoretical value and has the characteristics of high purity. Figure 1 These are the SEM images and element mapping images of the precursor obtained in step 5. From the images, it can be seen that the prepared precursor particles are uniform in size. From the mapping image, it can be seen that the three elements Ni, Mn, and O in the precursor are evenly distributed in the material.
[0054] Figure 2 This is the SEM image of the positive electrode material obtained in step 6. It can be seen from the figure that the positive electrode material prepared by this method exhibits a petal-like structure formed by primary particle assembly, the particle size is 2μm, and the particle structure is complete.
[0055] Embodiment 2:
[0056] Step 1, dissolve 0.03 mol urea (CON2H4), 0.002 mol Ni(CH3COO)2, and 0.006 mol Mn(CH3COO)2 in 10 mL of deionized water, and stir at room temperature for 10 min to obtain a uniform solution;
[0057] Step 2, adding 0.001 mol CH3COOLi and 60 mL ethanol to the solution obtained in step 1, and stirring to obtain a uniform solution;
[0058] Step 3, transferring the uniform solution obtained in step 2 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 140° C. for 24 h, and then cooling naturally to room temperature;
[0059] Step 4, washing the product obtained in step 3 with ethanol three times and filtering it, placing it in a forced air oven, and drying it at 80° C. for 2 h to obtain a solid powder;
[0060] Step 5, placing the solid powder obtained in step 4 into a muffle furnace and keeping it at 300° C. for 5 hours to obtain a precursor;
[0061] Step 6: Grind and mix 0.2 g of the precursor obtained in step 5 with 0.152 g of LiOH·H2O, put it into a muffle furnace, keep it at 700°C for 10 h, and cool it naturally to room temperature to obtain a petal-shaped Li 1.2 Ni 0.2 Mn 0.6 O2 positive electrode material.
[0062] Embodiment 3:
[0063] Step 1: 0.03 mol C6H 12 N4, 0.002 mol Ni(NO3)2, and 0.006 mol Mn(NO3)2 were dissolved in 20 mL of deionized water and stirred at room temperature for 10 min to obtain a homogeneous solution;
[0064] Step 2, adding 0.001 mol LiNO3 and 50 mL ethanol to the solution obtained in step 1, and stirring to obtain a uniform solution;
[0065] Step 3, transferring the uniform solution obtained in step 2 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 160° C. for 24 h, and then cooling naturally to room temperature;
[0066] Step 4, washing the product obtained in step 3 with ethanol three times and filtering it, placing it in a forced air oven, and drying it at 80° C. for 2 h to obtain a solid powder;
[0067] Step 5, placing the solid powder obtained in step 4 into a muffle furnace and keeping it at 1200° C. for 48 hours to obtain a precursor;
[0068] Step 6: Grind and mix 0.2 g of the precursor obtained in step 5 with 0.152 g of LiOH·H2O, put it into a muffle furnace, keep it at 1200°C for 72 hours, and cool it naturally to room temperature to obtain a petal-shaped Li 1.2 Ni 0.2 Mn 0.6 O2 positive electrode material.
[0069] Embodiment 4:
[0070] Step 1, dissolve 0.002 mol NiCl2 and 0.006 mol MnCl2 in 20 mL deionized water and stir at room temperature for 10 min to obtain a uniform solution;
[0071] Step 2, adding 0.001 mol KCl, 0.1 mol Na2CO3 and 50 mL ethanol to the solution obtained in step 1, and stirring to obtain a uniform solution;
[0072] Step 3, transferring the uniform solution obtained in step 2 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 160° C. for 24 h, and then cooling naturally to room temperature;
[0073] Step 4, washing the product obtained in step 3 with ethanol three times and filtering it, placing it in a forced air oven, and drying it at 80° C. for 2 h to obtain a solid powder;
[0074] Step 5, placing the solid powder obtained in step 4 into a muffle furnace and keeping the temperature at 480° C. for 5 h to obtain a precursor;
[0075] Step 6: Grind and mix 0.2 g of the precursor obtained in step 5 with 0.145 g of LiOH·H2O, put it into a muffle furnace, keep it at 780°C for 12 h, and cool it naturally to room temperature to obtain a petal-shaped Li 1.2 Ni 0.2 Mn 0.6 O2 positive electrode material.
[0076] Embodiment 5:
[0077] Step 1: 0.03 mol C6H 12 N4, 0.002 mol Ni(CH3COO)2, and 0.006 mol Mn(CH3COO)2 were dissolved in 5 mL of deionized water and stirred at room temperature for 10 min to obtain a homogeneous solution;
[0078] Step 2, adding 0.001 mol CH3COOLi and 50 mL ethanol to the solution obtained in step 1, and stirring to obtain a uniform solution;
[0079] Step 3, transferring the uniform solution obtained in step 2 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 160° C. for 12 h, and then cooling naturally to room temperature;
[0080] Step 4, washing the product obtained in step 3 with ethanol three times and filtering it, placing it in a forced air oven, and drying it at 80° C. for 2 h to obtain a solid powder;
[0081] Step 5, placing the solid powder obtained in step 4 into a muffle furnace and keeping the temperature at 480° C. for 5 h to obtain a precursor;
[0082] Step 6: Grind and mix 0.2 g of the precursor obtained in step 5 with 0.152 g of LiOH·H2O, put it into a muffle furnace, keep it at 780°C for 12 h, and cool it naturally to room temperature to obtain a petal-shaped Li 1.2 Ni 0.2 Mn 0.6 O2 positive electrode material.
[0083] Embodiment 6:
[0084] Step 1: 0.03 mol C6H 12 N4, 0.002 mol Ni(CH3COO)2, and 0.006 mol Mn(CH3COO)2 were dissolved in 30 mL of deionized water and stirred at room temperature for 10 min to obtain a homogeneous solution;
[0085] Step 2, adding 0.001 mol LiCl and 40 mL ethanol to the solution obtained in step 1, and stirring to obtain a uniform solution;
[0086] Step 3, transferring the uniform solution obtained in step 2 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 160° C. for 48 h, and then cooling naturally to room temperature;
[0087] Step 4, washing the product obtained in step 3 with ethanol three times and filtering it, placing it in a forced air oven, and drying it at 80° C. for 2 h to obtain a solid powder;
[0088] Step 5, placing the solid powder obtained in step 4 into a muffle furnace and keeping the temperature at 480° C. for 5 h to obtain a precursor;
[0089] Step 6: Grind and mix 0.2 g of the precursor obtained in step 5 with 0.152 g of LiOH·H2O, put it into a muffle furnace, keep it at 780°C for 12 h, and cool it naturally to room temperature to obtain a petal-shaped Li1.2 Ni 0.2 Mn 0.6 O2 positive electrode material.
[0090] Figure 3 It is the precursor material prepared in this example. As can be seen from the figure, after adding 0.001 mol LiCl, the morphology of the precursor is a more obvious petal-shaped microsphere structure with a particle size of 5 μm, and has the characteristics of uniform particle size distribution and complete particle structure.
[0091] Embodiment 7:
[0092] Step 1: 0.03 mol C6H 12 N4, 0.002 mol Ni(CH3COO)2, and 0.006 mol Mn(CH3COO)2 were dissolved in 60 mL of deionized water and stirred at room temperature for 10 min to obtain a homogeneous solution;
[0093] Step 2, adding 0.001 mol NaCl and 10 mL ethanol to the solution obtained in step 1, and stirring to obtain a uniform solution;
[0094] Step 3, transferring the uniform solution obtained in step 2 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 110° C. for 36 h, and then cooling naturally to room temperature;
[0095] Step 4, washing the product obtained in step 3 with ethanol three times and filtering it, placing it in a forced air oven, and drying it at 80° C. for 2 h to obtain a solid powder;
[0096] Step 5, placing the solid powder obtained in step 4 into a muffle furnace and keeping the temperature at 480° C. for 5 h to obtain a precursor;
[0097] Step 6: Grind and mix 0.2 g of the precursor obtained in step 5 with 0.152 g of LiOH·H2O, put it into a muffle furnace, keep it at 780°C for 12 h, and cool it naturally to room temperature to obtain a petal-shaped Li 1.2 Ni 0.2 Mn 0.6 O2 positive electrode material.
[0098] Embodiment 8:
[0099] Step 1: 0.8 mmol C6H 12 N4, 0.002 mol Ni(CH3COO)2, and 0.006 mol Mn(CH3COO)2 were dissolved in 30 mL of deionized water and stirred at room temperature for 10 min to obtain a homogeneous solution;
[0100] Step 2, adding 0.8 mmol CH3COOLi and 40 mL ethanol to the solution obtained in step 1, and stirring to obtain a uniform solution;
[0101] Step 3, transferring the uniform solution obtained in step 2 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 200° C. for 24 h, and then cooling naturally to room temperature;
[0102] Step 4, washing the product obtained in step 3 with ethanol three times and filtering it, placing it in a forced air oven, and drying it at 80° C. for 2 h to obtain a solid powder;
[0103] Step 5, placing the solid powder obtained in step 4 into a muffle furnace and keeping the temperature at 480° C. for 5 h to obtain a precursor;
[0104] Step 6: Grind and mix 0.2 g of the precursor obtained in step 5 with 0.152 g of LiOH·H2O, put it into a muffle furnace, keep it at 780°C for 12 h, and cool it naturally to room temperature to obtain a petal-shaped Li 1.2 Ni 0.2 Mn 0.6 O2 positive electrode material.
[0105] Embodiment 9:
[0106] Step 1: 0.032 mol C6H 12 N4, 0.002 mol Ni(CH3COO)2, and 0.006 mol Mn(CH3COO)2 were dissolved in 30 mL of deionized water and stirred at room temperature for 10 min to obtain a homogeneous solution;
[0107] Step 2, adding 0.08 mmol CH3COOLi and 40 mL ethanol to the solution obtained in step 1, and stirring to obtain a uniform solution;
[0108] Step 3, transferring the uniform solution obtained in step 2 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 160° C. for 24 h, and then cooling naturally to room temperature;
[0109] Step 4, washing the product obtained in step 3 with ethanol three times and filtering it, placing it in a forced air oven, and drying it at 80° C. for 2 h to obtain a solid powder;
[0110] Step 5, placing the solid powder obtained in step 4 into a muffle furnace and keeping the temperature at 480° C. for 5 h to obtain a precursor;
[0111] Step 6: Grind and mix 0.2 g of the precursor obtained in step 5 with 0.152 g of LiOH·H2O, put it into a muffle furnace, keep it at 780°C for 12 h, and cool it naturally to room temperature to obtain a petal-shaped Li 1.2 Ni 0.2 Mn 0.6 O2 positive electrode material.
[0112] Embodiment 10:
[0113] Step 1: 0.02 mol C6H 12 N4, 0.002 mol Ni(CH3COO)2, and 0.006 mol Mn(CH3COO)2 were dissolved in 30 mL of deionized water and stirred at room temperature for 10 min to obtain a homogeneous solution;
[0114] Step 2, adding 0.001 mol CH3COONa and 40 mL ethanol to the solution obtained in step 1, and stirring to obtain a uniform solution;
[0115] Step 3, transferring the uniform solution obtained in step 2 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 160° C. for 24 h, and then cooling naturally to room temperature;
[0116] Step 4, washing the product obtained in step 3 with ethanol three times and filtering it, placing it in a forced air oven, and drying it at 80° C. for 2 h to obtain a solid powder;
[0117] Step 5, placing the solid powder obtained in step 4 into a muffle furnace and keeping the temperature at 480° C. for 5 h to obtain a precursor;
[0118] Step 6: Grind and mix 0.2 g of the precursor obtained in step 5 with 0.152 g of LiOH·H2O, put it into a muffle furnace, keep it at 780°C for 12 h, and cool it naturally to room temperature to obtain a petal-shaped Li 1.2 Ni 0.2 Mn 0.6 O2 positive electrode material.
[0119] Figure 4 This is the SEM image of the positive electrode material obtained in step 6. It can be seen from the figure that the positive electrode material prepared by this method exhibits a cauliflower-like structure formed by primary particle assembly, and the particle size is 11 μm.
[0120] Embodiment 11:
[0121] Step 1: 0.03 mol C6H 12N4, 0.005 mol Ni(CH3COO)2, and 0.015 mol Mn(CH3COO)2 were dissolved in 30 mL of deionized water and stirred at room temperature for 10 min to obtain a homogeneous solution;
[0122] Step 2, adding 0.08 mmol CH3COOLi and 40 mL ethanol to the solution obtained in step 1, and stirring to obtain a uniform solution;
[0123] Step 3, transferring the uniform solution obtained in step 2 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 160° C. for 24 h, and then cooling naturally to room temperature;
[0124] Step 4, washing the product obtained in step 3 with ethanol three times and filtering it, placing it in a forced air oven, and drying it at 80° C. for 2 h to obtain a solid powder;
[0125] Step 5, placing the solid powder obtained in step 4 into a muffle furnace and keeping the temperature at 480° C. for 5 h to obtain a precursor;
[0126] Step 6: Grind and mix 0.2 g of the precursor obtained in step 5 with 0.0506 g of LiOH·H2O, put it into a muffle furnace, keep it at 780°C for 12 h, and cool it naturally to room temperature to obtain microspherical LiNi 0.5 Mn 1.5 O4 positive electrode material.
[0127] Figure 5 This is the SEM image of the positive electrode material obtained in step 6. It can be seen from the figure that the positive electrode material prepared by this method exhibits a microspherical structure formed by primary particle assembly, and the particle size is 15μm.
[0128] Embodiment 12:
[0129] Step 1: 0.02 mol C6H 12 N4, 0.002 mol Ni(CH3COO)2, and 0.006 mol Mn(CH3COO)2 were dissolved in 30 mL of deionized water and stirred at room temperature for 10 min to obtain a homogeneous solution;
[0130] Step 2, adding 0.008 mol CH3COOLi and 40 mL ethanol to the solution obtained in step 1, and stirring to obtain a uniform solution;
[0131] Step 3, transferring the uniform solution obtained in step 2 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 160° C. for 24 h, and then cooling naturally to room temperature;
[0132] Step 4, washing the product obtained in step 3 with ethanol three times and filtering it, placing it in a forced air oven, and drying it at 80° C. for 2 h to obtain a solid powder;
[0133] Step 5, placing the solid powder obtained in step 4 into a muffle furnace and keeping the temperature at 480° C. for 5 h to obtain a precursor;
[0134] Step 6: Grind and mix 0.2 g of the precursor obtained in step 5 with 0.152 g of LiOH·H2O and 0.0716 g of Na2CO3, put them into a muffle furnace, keep them at 850°C for 15 h, and cool them naturally to room temperature to obtain microspherical Li 0.2 Na 0.6 Ni 0.2 Mn 0.6 O2 positive electrode material.
[0135] Comparative Example:
[0136] Step 1: 0.03 mol C6H 12 N4, 0.002 mol Ni(CH3COO)2, and 0.006 mol Mn(CH3COO)2 were dissolved in 30 mL of deionized water and stirred at room temperature for 10 min to obtain a homogeneous solution;
[0137] Step 2, adding 40 mL of ethanol to the solution obtained in step 1, and stirring to obtain a uniform solution;
[0138] Step 3, transferring the uniform solution obtained in step 2 to a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 160° C. for 48 h, and then cooling naturally to room temperature;
[0139] Step 4, washing the product obtained in step 3 with ethanol three times and filtering it, placing it in a forced air oven, and drying it at 80° C. for 2 h to obtain a solid powder;
[0140] Step 5, placing the solid powder obtained in step 4 into a muffle furnace and keeping the temperature at 480° C. for 5 h to obtain a precursor;
[0141] Step 6: Grind and mix 0.2 g of the precursor obtained in step 5 with 0.152 g of LiOH·H2O, put it into a muffle furnace, keep it at 780°C for 12 h, and cool it naturally to room temperature to obtain a microspherical Li 1.2 Ni 0.2 Mn 0.6 O2 positive electrode material.
[0142] Figure 6It is the precursor material prepared in this comparative example. As can be seen from the figure, no alkali metal salt is added to the reaction system. The morphology of the prepared precursor is a microsphere structure assembled by polyhedral primary particles, and the particle size is about 15 μm. At the same time, it can be observed that the precursor is different from Example 6 ( Figure 3 ) compared to the original particle size distribution.
[0143] Test example:
[0144] The positive electrode material prepared based on supercritical carbon dioxide solution is applied to lithium-ion batteries: the Li 1.2 Ni 0.2 Mn 0.6 O2 positive electrode material, conductive carbon black and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 8:1:1, nitrogen methyl pyrrolidone (NMP) was added and stirred evenly, then coated on aluminum foil and dried in a vacuum oven at 80°C for 6 h to obtain a positive electrode sheet. Metallic lithium was used as the counter electrode, 1M lithium hexafluorophosphate (LiPF6) was dissolved in equal volumes of ethylene carbonate (EC) and dimethyl carbonate (DMC) as the electrolyte, and porous monolayer polypropylene (Celgard2500) was used as the diaphragm. A CR2025 lithium-ion battery was assembled in a glove box filled with argon, and its electrochemical properties were tested.
[0145] Battery performance test conditions: voltage window 2 ~ 4.8V (vs.Li + / Li), and the rate used in the charge and discharge performance test was 0.1C.
[0146] The test was repeated using the positive electrode material obtained in the comparative example as a control.
[0147] Figure 7 1 is an electrochemical performance diagram of the positive electrode material obtained in Example 1 and step 6 of the comparative example applied to a button battery. It can be seen from the figure that the first cycle discharge capacity of the battery assembled with the positive electrode material of Example 1 is 256.73 mAh / g. It can be seen from the figure that compared with the comparative example, the positive electrode material obtained in Example 1 has a higher electrochemical capacity.
[0148] The positive electrode material of Example 6 and the positive electrode material of the comparative example were assembled into batteries according to the above method, and the cycle performance test was carried out. The results are as follows: Figure 8 As shown in the figure, it can be seen that, compared with the comparative example, the electrochemical stability of the positive electrode material obtained in Example 6 is significantly improved, and the capacity retention rate after 200 cycles is as high as 93%.
[0149] The above is only one embodiment of the present invention, not all or the only embodiment. Any equivalent changes made to the technical solution of the present invention by ordinary technicians in this field after reading the specification of the present invention are covered by the claims of the present invention.
Claims
1. A method for preparing a cathode material based on a supercritical carbon dioxide solution, characterized in that: The following steps are involved: S1, adding a carbon dioxide initiator, a transition metal salt, an alkali metal salt and an alcohol solvent into water, mixing, and obtaining a mixed solution; the alkali metal salt is one or more of LiNO3, LiOH, CH3COOLi and LiCl; the molar ratio of the alkali metal salt to the transition metal salt is (0.01-1):1; the carbon dioxide initiator is one or more of urea, urotropine, Na2CO3, NaHCO3, dry ice, NH4HCO3 and oxalic acid; the alcohol solvent is an alcohol having a carbon number of less than ten; S2, subjecting the mixed solution to a hydrothermal reaction at a temperature of 110-200 °C for a reaction time of 20-28 h, washing and drying the obtained product to obtain a hydrothermal product; S3, calcining the hydrothermal product at high temperature to obtain a precursor; S4, mixing the precursor with lithium salt, and calcining at high temperature to obtain the positive electrode material.
2. The method for preparing a cathode material based on a supercritical carbon dioxide solution according to claim 1, characterized in that: In S1, the transition metal salt is one or more of NiCl2, CoCl2, MnCl2, Ni(NO3)2, Co(NO3)2, Mn(NO3)2, Ni(CH3COO)2, Co(CH3COO)2 and Mn(CH3COO)2.
3. The method for preparing a cathode material based on a supercritical carbon dioxide solution according to claim 1, characterized in that: In S1, the molar ratio of the carbon dioxide initiator to the transition metal salt is (0.1~4):1; the volume ratio of the alcohol solvent to water is 1:(0.1~10).
4. The method for preparing a cathode material based on a supercritical carbon dioxide solution according to claim 1, characterized in that: In S3, high temperature calcination is carried out in air or oxygen atmosphere, the calcination temperature is 300~1200℃, and the time is 5~48h.
5. The method for preparing a cathode material based on a supercritical carbon dioxide solution according to claim 1, characterized in that: In S4, the lithium salt is one or more of LiNO3, LiOH, Li2CO3, CH3COOLi and LiCl.
6. The method for preparing a cathode material based on a supercritical carbon dioxide solution according to claim 1, characterized in that: In S4, high temperature calcination is carried out in air or oxygen atmosphere, the calcination temperature is 700~1200℃, and the time is 10~72h.
7. A positive electrode material obtained by the method for preparing a positive electrode material based on a supercritical carbon dioxide solution according to any one of claims 1 to 6.
8. A secondary battery, characterized in that: Comprising the positive electrode material as claimed in claim 7.
Citation Information
Patent Citations
Preparation method and application of high-tap-density positive electrode material for lithium ion battery
CN106058170A
Spherical rich-lithium manganese-base positive electrode material using lanthanum for partially replacing manganese and preparation method thereof
CN106129400A
Positive ion based morphological regulation type ferro-manganese composite oxide material preparation method and application thereof
CN109289866A